2022
DOI: 10.1101/2022.07.15.500120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic functional interrogation of SARS-CoV-2 host factors using Perturb-seq

Abstract: Numerous host factors of SARS-CoV-2 have been identified by screening approaches, but delineating their molecular roles during infection and whether they can be targeted for antiviral intervention remains a challenge. Here we use Perturb-seq, a single-cell CRISPR screening approach, to investigate how CRISPR interference of host factors changes the course of SARS-CoV-2 infection and the host response in human lung epithelial cells. Our data reveal two classes of host factors with pronounced phenotypes: factors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…However, aside from this study and a previous OPS of Sendai virus infection (Carlson et al, 2023), high-content profiling screens of host-pathogen interactions have been limited. Notable recent examples include targeted transcriptome screens that revealed perturbation-induced changes in transcriptional trajectories upon HCMV (Hein & Weissman, 2022) and SARS-CoV-2 (Sunshine et al, 2022) infection. Importantly, high-content perturbation screens like these and that which we report here did not require a priori specification of phenotypes of interest but rather resulted in rich data resources that can be mined to rapidly generate and investigate hypotheses based on primary screening data alone (Bock et al, 2022), provided the achievement of adequate quantitative performance of the perturbation and phenotyping steps, and adequate cell sampling.…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from this study and a previous OPS of Sendai virus infection (Carlson et al, 2023), high-content profiling screens of host-pathogen interactions have been limited. Notable recent examples include targeted transcriptome screens that revealed perturbation-induced changes in transcriptional trajectories upon HCMV (Hein & Weissman, 2022) and SARS-CoV-2 (Sunshine et al, 2022) infection. Importantly, high-content perturbation screens like these and that which we report here did not require a priori specification of phenotypes of interest but rather resulted in rich data resources that can be mined to rapidly generate and investigate hypotheses based on primary screening data alone (Bock et al, 2022), provided the achievement of adequate quantitative performance of the perturbation and phenotyping steps, and adequate cell sampling.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by studies by Sunshine et al, who identified NFKBIA in a Perturb-Seq study as a host protein supporting viral replication. 36 …”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by studies by Sunshine et al, who identified NFKBIA in a Perturb-Seq study as a host protein supporting viral replication. 36 It remains to be determined what the relevant upstream and downstream signals of this proviral phenotype are and whether the continuous presence of NF-κB in the cell nucleus provides benefits for the SARS-CoV-2 lifecycle. Our findings indicate that after overexpression of the mutant IκBα protein, nuclear p65 levels were lower in infected cells, supporting a model in which IκBα promotes viral infection by constraining, albeit not completely, the well-known antiviral activities of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect the overexpression of interferon (IFN) and IFN-stimulated genes (ISGs) in these populations, likely a consequence of virus-mediated repression at the protein level 6 . Previous studies have shown that cytokine production in virus-infected populations is often confined to small subpopulations of abortively infected cells [33][34][35] . Clustering cells purely based on their transcriptome patterns indeed revealed that stress-related and cytokine transcripts are concentrated in a small cluster of infected cells (Fig.…”
Section: Single-cell Resolution Of the Transcriptional Landscape In V...mentioning
confidence: 99%